Pancreaticoduodenectomy in patients < 75 years versus ≥ 75 years old: a comparative study - ERGENÇ, MUHAMMER; UPRAK, TEVFİK KIVILCIM; KARPUZ, ŞAKİR; COŞKUN, MÜMİN; YEGEN, ŞEVKET CUMHUR; ATICI, ALİ EMRE (My University, 2024)
Objective: This study aimed to compare the postoperative outcomes of < 75-year-old patients and ≥ 75-year-old patients who underwent pancreaticoduodenectomy (PD) for pancreatic head and periampullary region tumors. Methods: Patients who underwent PD in our hospital between February 2019 and December 2023 were evaluated. Demographics, Eastern Cooperative Oncology Group Performance Status (ECOG-PS) scores, American Society of Anesthesiologists (ASA) scores, comorbidities, hospital stays, complications, and clinicopathological features were analyzed. Patients were divided into < 75 years (Group A) and ≥ 75 years (Group B) groups and compared. Results: The median age of the entire cohort (n = 155) was 66 years (IQR = 16). There was a significant difference between Group A (n = 128) and Group B (n = 27) regarding the ECOG-PS and ASA scores. There was no significant difference between the groups regarding postoperative complications. The 30-day mortality rate was greater in Group B (p = 0.017). Group B had a cumulative median survival of 10 months, whereas Group A had a median survival of 28 months, with a statistically significant difference (p < 0.001). When age groups were stratified according to ECOG-PS, for ECOG-PS 2–3 Group A, survival was 15 months; for ECOG-PS 2–3 Group B, survival was eight months, and the difference was not statistically significant (p = 0.628). Conclusions: With the increasing aging population, patient selection for PD should not be based solely on age. This study demonstrated that PD is safe for patients older than 75 years. In older patients, performance status and the optimization of comorbidities should be considered when deciding on a candidate’s suitability for surgery.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Geriatri; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Geriatrics; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; GERİATRİ ve GERONTOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; BIOCHEMISTRY & MOLECULAR BIOLOGY; GERIATRICS & GERONTOLOGY; Yaşlanma; Geriatri ve Gerontoloji; Aging; Geriatrics and Gerontology; Elderly; Geriatric surgery; Pancreatectomy; Pancreatic adenocarcinoma; Performance status; Survival